Foreign policy factor in State-Church relations in the Soviet Union during World War II and early post-war - Ibragimov, Ruslan Rustamovich; Fazliev, Aivaz Minnegosmanovich; Samatova, Chulpan Khamitovna; Alimov, Boturzhon Khamidovich (Cuestiones Políticas, 2020)
The objective of the research was to study Russian State and Orthodox church relations in the context of world war II and the early post-war years. The line of this article is due to the important role of the Russian Orthodox Church in the history, modern political and cultural life of Russia. In this sense, the period of State-Church relations in the USSR during world war II, known in Russia as a great patriotic war, is of great scientific interest because it was the time when the government was forced to make adjustments to its religion policy. Methodologically based on a wide range of documentary sources, the authors of the article have identified the place and role of the Russian Orthodox Church in the foreign policy of the USSR during the approach. In this sense, it is felt that the role of the Russian Orthodox Church in building relations with the allies of the anti-Hitler coalition and its place in the expansion of the Soviet political system in Eastern Europe was of paramount importance as a foreign policy factor.